DOMINANT HABITUS IN HARUKI MURAKAMI’S NOVEL “HEAR THE WIND SING” - Triandari, Meli; Abdullah, Abdullah; Mustikawati, Yunitari (Faculty of Languages and Literature, Universitas Negeri Makassar, 2024)
This research discussed how dominant habitus is represented in Haruki Murakami’s Novel “Hear the Wind Sing”. This research aims to discover dominant habitus represented in Haruki Murakami’s Novel “Hear the Wind Sing”. To analyze dominant habitus, this research used concept habitus, field, and capital through strategy of domination theory by Pierre Bourdieu. This research applied a descriptive qualitative method to describe the data that there is a dominant habitus in Haruki Murakami’s novel “Hear the Wind Sing”. This is represented through the lifestyle of the characters in Haruki Murakami’s novel “Hear the Wind Sing”, the dominant habitus in this research are, drinking beer, going to the bar, reading books, listening to western music and vacationing in luxury places.